Analisis Yuridis Penegakan Hukum pada Pelaku Tindak Pidana Perjudian di Kabupaten Magelang - Laila Nurul Hidayati; Pinky Aruna Iswandarie; Ilham Jeryawan; Susi Rosiana; Lia Sari; Rani Pajrin (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
As a country based on legal norms and principles, Indonesia strictly prohibits gambling through statutory regulations. Gambling is a criminal act that can cause harm to society both directly and indirectly. However, in fact, gambling is still widespread, one of which is in the Magelang Regency area, Central Java. The aim of this research is to find out what factors are behind criminal acts of gambling based on the decision of the Mungkid District Court in the January 2025 period and efforts to enforce the law against criminal acts of gambling with the research method used is a normative legal research method with a qualitative analysis approach. The results of this research show that psychological, difficult economic conditions, where people are looking for quick ways to get money, as well as the influence of the social environment that makes gambling free are the main factors for perpetrators to gamble. Therefore, all law enforcement efforts are needed, including socializing the dangers of gambling, operations to control gambling perpetrators by law enforcement officials, as well as enforcing legal sanctions for criminal acts of gambling.